Mudanças na natureza do comércio no mundo conectado através do e-commerce - Varandas, Agostinho Ferro Pinto (2001)
The Internet has taken the world by storm. It has eliminated the barriers of technology, and unlocked the doors to electronic commerce and the 'Virtual Economy'. It has given us a glimpse into the future of 'Business' itself, and it has created a bewildering variety of choices in our personal and professional lives. It has taken on a life of its own, and we are all frantically trying to keep up. Many overwhelmed companies are asking questions like: 'What should our Internet Strategy be?' Or 'How do we put our business on the Internet like everybody else is doing?' or 'How do we use this thing to make money without spending any?'. These questions may seem reasonable on the surface, but they miss the point because they focus on the technologies rather than the core issues of conducting day-to-day business. The Internet can indeed offer fast returns in marketing reach, speed, director consumer sales and so on, and many companies are using it to good advantage, but the highest and best use of any such technology is to support, enhance and even re-invent the fundamentals of general business practice. When the initial excitement is over, and companies gain experience and confidence with the new business models, this larger view will begin to assert itself. Companies will then start to position their 'Internet Strategies' in context of where the business world itself is going over time, and how they can prepare for what is to come. Until now, the business world has been very fragmented, its collective progress limited (in part) by the inability to communicate within and between companies. Now that the technical remedy seems to be at hand and standards are beginning to emerge, we are starting to see a trend toward consolidation, cooperation, and economic synergy. Companies are improving their internal business processes with Intranets, and Electronic Commerce initiatives have sprung up using EDI, the World Wide Web, E-Mail, secure credit card payments and other tools. Companies are using the Internet to talk to each other and to sell their goods and services to the end consumer. Like Berlin, the walls are coming down because they have to. Electronic 'Communities of Common Interest' are beginning to surface, with the goal of supporting and aligning similar industries (such as Government, Insurance, Transportation and Health care) or similar business functions (such as Purchasing, Payments, and Human Resources). As these communities grow and mature, their initial scope will broaden and their spheres of influence will expand. They will begin to overlap into other communities, creating a synergistic effect and reshaping the conduct of business. The business world will undergo a gradual evolution toward globalization, driven by economic imperatives and natural selection in the marketplace, and facilitated by Electronic Commerce and Internet technologies. The business world 'beyond 2000' will have a substantially different look and feel than that which we see today.